Valorization of methane from environmental engineering applications: A critical review. (15th December 2020) - Jawaharraj, Kalimuthu; Shrestha, Namita; Chilkoor, Govinda; Dhiman, Saurabh Sudha; Islam, Jamil; Gadhamshetty, Venkataramana
Highlights: A current body of knowledge on methanotrophs for CH4 mitigation was reviewed. Point sources and feasibility of CH4 in wastewater treatment plants. CH4 oxidation can be coupled with a reduction of O2, NO3 −, and electrodes. Bioproducts from CH4 find use in many environmental engineering applications. Methanotrophs can valorize stranded CH4 from hydraulically fractured shales. Abstract: Wastewater and waste management sectors alone account for 18% of the anthropogenic methane (CH4 ) emissions. This study presents a critical overview of methanotrophs ("methane oxidizing microorganisms") for valorizing typically discarded CH4 from environmental engineering applications, focusing on wastewater treatment plants. Methanotrophs can convert CH4 into valuable bioproducts including chemicals, biodiesel, DC electricity, polymers, and S-layers, all under ambient conditions. As discarded CH4 and its oxidation products can also be used as a carbon source in nitrification and annamox processes. Here we discuss modes of CH4 assimilation by methanotrophs in both natural and engineered systems. We also highlight the technical challenges and technological breakthroughs needed to enable targeted CH4 oxidation in wastewater treatment plants. Graphical abstract: Image, graphical abstract